Lumped Equivalent Models of Narrowband Antennas and Isolation Enhancement in a Three Antennas System - Nella, Anveshkumar; Gandhi, Abhay (Společnost pro radioelektronické inženýrství, 2018)
This paper initially discusses lumped equivalent models of narrowband (NB) antennas and then presents a technique to enhance isolation between UWB and NB antennas of the three antennas system. The proposed models are able to yield similar S-parameter performance as that of NB antennas at their resonant frequencies. Also, a good match is observed at other frequencies between the HFSS and AWR results. This paper reports an isolation enhancement technique using microstrip lines. The proposed approach enhances a minimum isolation of 11dB at respective resonant frequencies. This paper also reports lumped equivalent models of dual band reject filters (DBRFs). Proposed geometry is fabricated and tested. Experimental result shows an agreement between the simulated and measured results.
Keywords: Band reject filter; dual bands; isolation; lumped equivalent model; microstrip lines.